Viscoelastic behavior of yellow pitahaya treated with 1-MCP (2016)
Foods may have both solid and liquid properties, and are described as viscoelastic products. Knowledge on such viscoelastic features is very useful for quality control and/or food stability. The purpose of this work was to evaluate the effect of the application of 1-MCP on the viscoelastic properties of minimally processed yellow pitahaya during refrigeration storage, by using a stress relaxation test. Viscoelastic parameters were determined through Generalized Maxwell and Peleg’s rheologic models. Both rheological models proved suitable to predict viscoelastic behavior; however, Peleg’s model better described this behavior. Samples of treated and non-treated pitahaya with 1- MCP decreased their elastic behavior (firmness decrease) during storage. Fruit treated with 1-MCP showed a greater elastic component than non-treated samples during storage. These two rheological models were suitable for predicting the viscoelastic behavior, however